2000
DOI: 10.1007/pl00007943
|View full text |Cite
|
Sign up to set email alerts
|

Normal liver function in women in the general Japanese population subjected to environmental exposure to cadmium at various levels

Abstract: Overall, it seemed prudent to conclude that liver function as not disturbed by the current environmental exposure to Cd in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Previously, liver damage by Cd was reported in experimental animal studies, both acute and chronic (Dudley et al 1984(Dudley et al , 1985Habeebu et al 2000). However, liver toxicity in Cd-exposed workers has been rarely reported (Attia et al 2009; ATSDR 2012; Tomei et al 2013), and no evidence for Cd-induced liver damage was found in the general Japanese population (Ikeda et al 1997(Ikeda et al , 2000. During the last decade, several epidemiology studies have reported liver damage due to environmental exposure to low levels of Cd in the general population (Hyder et al 2013;Kang et al 2013;Chung et al 2020;Hong et al 2021), representing a grave concern to human health.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, liver damage by Cd was reported in experimental animal studies, both acute and chronic (Dudley et al 1984(Dudley et al , 1985Habeebu et al 2000). However, liver toxicity in Cd-exposed workers has been rarely reported (Attia et al 2009; ATSDR 2012; Tomei et al 2013), and no evidence for Cd-induced liver damage was found in the general Japanese population (Ikeda et al 1997(Ikeda et al , 2000. During the last decade, several epidemiology studies have reported liver damage due to environmental exposure to low levels of Cd in the general population (Hyder et al 2013;Kang et al 2013;Chung et al 2020;Hong et al 2021), representing a grave concern to human health.…”
Section: )mentioning
confidence: 99%
“…A few studies have reported the effect of Cd exposure on liver damage in industrial workers, but the results did not support that Cd was a causative agent of liver injury in occupationally Cd-exposed workers(Attia et al 2009;Tomei et al 2013). Furthermore,Ikeda et al (1997Ikeda et al ( , 2000 reported that environmental Cd exposure did not affect liver function among general Japanese females, despite relatively high Cd levels in the blood (GM of 2.17 and 1.76 µg/L) and urine (1.98 and 3.94 µg/g of creatinine). Similarly, no association between blood BCd and ALT elevation was observed in the US adult general population(Cave et al 2010).…”
mentioning
confidence: 99%
“…& Ivanenko, A.A., 2013). In addition, the increasing production and usage of cadmium compounds lead to a sufficient enhancement of cadmium concentration in the environment (Ikeda et al, 2000;Aghajanian & Skalny, 2001;Lyon et al, 2002;Onishchenko, 2003;Stepanova, 2003 ). Alcohol has complex toxic effects on the human organism (Gerke, P., Hapke, U., Rumpf, H. J., & John, U., 1997;McIntosh, C., & Chick, J.,2004).…”
Section: Introductionmentioning
confidence: 99%
“…4 Further, Cd causes multiple organ injuries after acute and chronic exposure to higher doses. 2 One epidemiological study 5 reported that the incidence of human hepatic dysfunction does not correlate with levels of exposure to Cd. It is possible that lipopolysaccharide (LPS) is responsible for the lack of correlation between the incidence of human hepatic dysfunction and the levels of Cd exposure.…”
Section: Introductionmentioning
confidence: 99%